EU and OSCE Cooperation in the Russia-Ukraine Conflict: Impacts and Limitations - Mahilaj, Sara (European Scientific Journal, ESJ, 2023)
The ongoing conflict between Russia and Ukraine, which began in 2014, has been a major challenge to regional and international security. In response, the European Union (EU) and the Organization for Security and Cooperation in Europe (OSCE) have been actively involved in efforts to promote peace, stability, and security in the region. In light of the ongoing conflict between Russia and Ukraine, this paper examines the relationship between the European Union (EU) and the Organization for Security and Cooperation in Europe (OSCE). The EU and OSCE have been actively engaged in conflict resolution efforts, with a focus on diplomatic and economic sanctions against Russia. However, the intricate political and military dynamics at play as well as the wider geopolitical tensions between Russia and the West have limited the efficacy of these efforts. This paper aims to examine the impacts and limitations of EU and OSCE cooperation in addressing the conflict between Russia and Ukraine. The research question that follows this paper is on how has the relationship between the EU and OSCE been impacted by the conflict between Russia and Ukraine, and what are the challenges and opportunities facing these organizations in their efforts to promote peace and stability in the region? Ultimately, the paper argues that a comprehensive and inclusive approach is needed to effectively address the conflict and promote sustainable peace and stability in the region.